LEXICAL AND SYNTACTIC MEANS OF EXPRESSING A SLOGAN IN A FRENCH-LANGUAGE ADVERTISING TEXT - Lutsyk , Nataliia; Voronko , Halyna; Kruk , Zoriana (Philological Treatises, 2023)
The article deals with lexical and syntactic means of expressing the slogan in the French-language advertising text. Particular attention is paid to the development of advertising as a linguistic phenomenon. The works of Ukrainian and foreign scientists studying the structural and functional characteristics of advertising texts and the peculiarities of their creation are analyzed. The article examines the functional and stylistic status of the advertising slogan and clarifies the structural and syntactic features of French-language advertising. The material of the study is advertising slogans obtained by continuous sampling method from French-language websites of trading companies. The research uses the structural-linguistic method, lexical-semantic and syntactic analysis. Emphasis is placed on the use of nominative sentences as one of the most productive ways of creating slogans. The article highlights prepositive definitions, postpositive constructions and cases of their joint use used in order to emphasize the indication of the target audience and the possibility of specifying the idea of a unique trade offer. It is noted that the main element of the advertising text is the verb, which gives the sentence dynamism, movement, and creates the appearance of action. Analysis of slogans in verb forms of imperative and indicative showed that the pragmatic message of such syntactic structures is usually a call to action, advice, instruction. It was found that the use of infinitive sentences in advertising texts is quite common in French-language discourse as one of the most optimal forms of motivation, since the semantics of the infinitive expression is more easily combined with the meaning of necessity and inevitability. The use of slogans in the form of two-part sentences, the structure of advertising statements of which is less concise, is analyzed. As a result of the study, it was found that the syntactic feature of the slogan is the tendency to dominate nominative constructions in order to create an association with the trademark.